FORMATION OF LOCAL ELECTRIC ENERGYSYSTEMS in the composition of THE UNIFIED ENERGY SUPPLY SYSTEM - KOZACHUK, OLEG; LEZHNIUK, PETRO (Herald of Khmelnytskyi National University. Technical sciences, 2024)
At present, renewable sources of energy (RSE) are geographically diffused in energy supply systems, which complicates the formation of local electric energy systems (LEES), which operating in normal modes in parallel with the energy system as balancing groups, in extreme cases can operate in isolation in autonomous mode. However, the diffuse distribution of RSE does not allow for the effective formation of LEES in such a way that they ensure the required level of reliability of electricity supply to electricity consumers. The article proposes to integrate RSE into distribution power grids in the form of separate microgrid (MG), which is a key part of the transition to a power grid operating on the principles of SMART Grid. Local MGs, in addition to generation sources and consumers, also have the means to accumulate a certain amount of energy. To ensure the technical and economic efficiency, MGs are combined into an intelligent control system, which allows for more rational use of MG resources, efficient interaction with the distribution grid, and the use of active electricity consumers in the process of balancing the LEES mode. The paper proposes a hierarchical structure of the intellectual system of LEES. Thus structured, LEES with intelligent power grids can not lose RSE during the limitation of centralized power supply, but fully use their advantages together with energy storage systems for reliable power supply to consumers. Thanks to the intelligent system proposed in this paper, the LEES implements the principles of SMART Grid and functions as an informative energy system. The LEES formed in this way can operate as a balancing group within the ESS, performing the tasks of the distribution system operator depending on the voltage and power of its MG components. Since LEES are a part of the ESS, they operate under the conditions and according to the rules, without disrupting the functioning of the ESS, which currently provides a stable power supply. This applies to all modes of operation of LEES.
Keywords: local electric energy systems; autonomous mode; renewable sources of energy; intelligent control system